2023
DOI: 10.7759/cureus.40653
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Armed Conflicts on Public Health Infrastructure and Services in Oromia, Ethiopia

Abstract: BackgroundOromia is the largest national regional state in the Ethiopian federation. It covers over a third of the country's landmass. In terms of sheer geography, Oromia is about the size of the sovereign European state of Germany. Demographically, Oromia closely matches with Poland among other European countries. Since early 2019, there are actively ongoing armed conflicts in Oromia damaging the public health infrastructure and hampering the provision of healthcare services. ObjectiveThe objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Community initiatives, including expanded indoor residual spraying, rapid diagnosis, increased access to insecticide-treated nets, and enhanced awareness, may have contributed to the earlier decline. Conversely, disruptions caused by the COVID-19 pandemic, ongoing armed conflicts, and unrest may explain the sudden surge in malaria cases in 2022/23 [ 17 , 24 26 ]. Consistent with the current findings, a different study reported a positive correlation between malaria resurgence and armed conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community initiatives, including expanded indoor residual spraying, rapid diagnosis, increased access to insecticide-treated nets, and enhanced awareness, may have contributed to the earlier decline. Conversely, disruptions caused by the COVID-19 pandemic, ongoing armed conflicts, and unrest may explain the sudden surge in malaria cases in 2022/23 [ 17 , 24 26 ]. Consistent with the current findings, a different study reported a positive correlation between malaria resurgence and armed conflict.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi [ 20 ], as well as the emergence of diagnostic failures for P. falciparum [ 21 23 ]. Ongoing armed conflicts in different parts of Ethiopia, including Northern Ethiopia, Oromia, and Benishangul-Gumuz, coupled with population displacement due to drought, impede efforts to control and eliminate malaria [ 17 , 24 26 ]. Several risk factors arise in areas affected by conflict, including breakdown of health centres, displacement of large non-immune populations to endemic areas and resettlement of refugees to deteriorated environments that favour vector breeding [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 The effects of these conflicts on public health infrastructure and the resulting limitations on providing essential public healthcare services would be significant. 11 This has alarmingly led to a high number of deaths among children due to malaria and anemia. This little girl had been experiencing symptoms such as fatigue, vomiting, cough, loss of appetite, and dizziness for a week.…”
Section: Case Presentation Casementioning
confidence: 99%
“…It is also vital to provide urgent humanitarian assistance to the affected population. 11 It is crucial to conduct a case series on low hemoglobin levels in malaria and anemia areas for several reasons. Firstly, it can provide valuable insights into the impact of these conditions on hemoglobin levels, which can aid in understanding the severity and progression of the diseases.…”
Section: Introductionmentioning
confidence: 99%